Tingkat Literasi Kesehatan Pasien Diabetes Mellitus Tipe 2 Di Puskesmas Kota Tomohon - Vina Putri Patandung; Kusrini Kadar; Kadek Ayu Erika (Interest : Jurnal Ilmu Kesehatan, 2018)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic disease with high level of complexity that requires extensive education and self-care management. The demands on individuals with T2DM are complicated by the fact that self-care often depends on printed educational materials and high health literacy skills. Every individual who needs health information and services also needs health literacy skills to find health information and services, communicating needs, respond to and using the information and obtaining health services, understanding health information, and finding realible health information and services to suit all needs, making the right decision to act. This study aims to determine the level of functional, communicative, and critical health literacy of T2DM patients at Pangolombian and Kakaskasen Public Health Centre of Tomohon City, as well as factors related to the level of health literacy. Method: Quantitative descriptive to describe the level of health literacy and correlation to see factors related to the patient's health literacy level. The sample of this study was a patient of T2DM who followed prolanis, amounted to 34 people, determined by using purposive sampling. Data were obtained by interview and using demographic characteristics questionnaire and Functional, Communicative, and Critical Health Literacy questionnaires. Result: Generally, health literacy level of T2DM patients is still low both for functional, communicative, and critical. This can happen because of various factors but the most related is the low access to health information and patient education level. Conclusion: The results of this study showed that health literacy level of T2DM patient in Tomohon city is still very low. This happened because access to health information is still less obtained by patients and also their education level is still low. These results can be used as recommendations for health workers to pay more attention to how to educate patients who should be adjusted to the level of education so that the information provided can be put to good use by the patient.